Agency Staffing and Hospital Financial Performance: Insights and Implications - Pradhan R; Beauvais B; Ramamonjiarivelo Z; Dolezel D; Wood D; Shanmugam R (Dove Medical Press, 2024)
Rohit Pradhan,1 Bradley Beauvais,1 Zo Ramamonjiarivelo,1 Diane Dolezel,2 Dan Wood,3 Ramalingam Shanmugam1 1School of Health Administration, Texas State University, San Marcos, TX, 78666, USA; 2Department of Health Informatics and Information Management, Texas State University, Round Rock, TX, 78665, USA; 3Army-Baylor University MHA/MBA Program, U.S. Army Medical Center of Excellence, San Antonio, TX, 78234, USACorrespondence: Rohit Pradhan, ENC 264, School of Health Administration, Texas State University, 601 University Dr, San Marcos, TX, 78666, USA, Tel +1 (512) 245-6529, Email pradhan@txstate.eduIntroduction: Staffing is critical to hospital performance. However, in recent years, hospitals have struggled with severe staffing shortages, forcing them to rely on expensive agency staff to meet urgent patient care needs. This substitution of agency staff for permanent employees has raised concerns over its potential impact on financial stability. This study investigated the association of agency labor with hospital financial performance.Methods: Utilizing tenets from agency theory and transaction cost theory, data for the calendar year 2022 for active short-term acute care hospitals (n=2771) in the United States were analyzed using multivariable linear regression analysis. Hospital financial performance was assessed using three variables: net patient revenue, operating revenue per bed, and operating expense per bed. The independent variable was agency labor cost, representing the total expenditure on agency labor. Additionally, organizational and market-level control variables that may independently affect hospital financial performance were included.Results: Our regression findings indicated that agency labor cost was significantly associated with all three dependent variables: net patient revenue (β = 0.224, p < 0.001), operating revenue per bed (β = 0.042, p < 0.001), and operating expense per bed (β = 0.032, p < 0.001).Discussion: The results indicated that increased agency labor was associated with higher revenues, but it also corresponded with increased expenses. Therefore, hospitals should strategically use agency staffing to meet immediate operational needs while remaining cognizant of its financial implications. The judicious use of agency labor can help hospitals balance the benefits of increased revenue against higher costs, while ensuring that they still meet immediate patient needs.Keywords: agency staff, contract labor, hospital financial performance, healthcare staffing